Análise e caracterização do material particulado atmosférico fino em uma região metropolitana de Natal-RN - Duarte, Ediclê de Souza Fernandes (2016)
This study had as objective a chemical characterization of PM 2.5 aerosol collected by a Harvard Sampler in Natal, capital of the state of Rio Grande do Norte, Brazil. Sampling was performed daily using a 37 mm quartz filters. Gravimetric techniques were used, as well as quantification of Black Carbon (BC), and X-ray fluorescence analysis. Also, simulations were made to understand dispersion and deposition of the particulate matter using trajectories of the HYSPLIT model in order to know the origin and fate of these pollutants in the atmosphere. The sampling of PM2.5 occurred continuously for the period from March 03, 2015 to December 2015. The results showed that the monthly averages ranged from 2.98 a 14.43 μg/m3 for the analyzed PM2.5 period, while the daily average concentrations ranged from 0.25 a 62,79 μg/m3 for PM 2.5 during the same period. The BC analysis showed that the month of June showed the highest peak of BC concentration of approximately 3.42 μg/m3. Through the BC concentration analysis by weekdays it was observed in the box plot graphs that the concentrations on Saturday and Sunday tend to be smaller than the other days of the week. This can be associated with the effect of the reduction in vehicle traffic during these days. The days from Monday through Friday, showed the highest dispersion of BC concentrations in which the interquartile range was greater than the days of Saturday and Sunday, showing that BC concentrations are larger during the week than on weekends since vehicle traffic is more intense. From the samples obtained by the fine particulate sampler and analysis by X-ray fluorescence (EDX) it was possible to identify the elements with the highest concentration present in the filters: S, K, Si, Al, Cl, Fe, P, Ca, Mn and Ca. Most of these components were of anthropogenic origin according to the enrichment factor, and Na, Mg, Sn, Zn, Al, Fe and Ti are from natural sources. The results of PM2.5 concentrations were statistically related to meteorological variables for information about the effects of these variables on the concentration.